What time is it? Roberto Schwarz and criticism of contemporary - Leonardo Octavio Belinelli de Brito (Revista de Ciências Humanas, 2017)
The article analyzes the formulations of Roberto Schwarz about the world and Brazilian contemporary, which are inseparable. We will take as objects of analysis some of the tests that the critic published in several of his books, from the householder and other studies , passing the time ?, by Brazilian sequences and reaching Martinha versus Lucrezia. The interpretation proposed text is that Schwarz's work can be interpreted as a constant reflection - so always up to date - on the impasses of Brazilian modernization In this sense, the work will also seek to observe how the materialist dialectic method used by Schwarz , It may indicate the connections between the various plans that make up the national life.